N-butyldeoxynojirimycin delays motor deficits, cerebellar microgliosis, and Purkinje cell loss in a mouse model of mucolipidosis type IV - Boudewyn, Lauren C; Sikora, Jakub; Kuchar, Ladislav; Ledvinova, Jana; Grishchuk, Yulia; Wang, Shirley L; Dobrenis, Kostantin; Walkley, Steven U (Neurobiology of disease, 2017)
Mucolipidosis type IV (MLIV) is a lysosomal storage disease exhibiting progressive intellectual disability, motor impairment, and premature death. There is currently no cure or corrective treatment. The disease results from mutations in the gene encoding mucolipin-1, a transient receptor potential channel believed to play a key role in lysosomal calcium egress. Loss of mucolipin-1 and subsequent defects lead to a host of cellular aberrations, including accumulation of glycosphingolipids (GSLs) in neurons and other cell types, microgliosis and, as reported here, cerebellar Purkinje cell loss. Several studies have demonstrated that N-butyldeoxynojirimycin (NB-DNJ, also known as miglustat), an inhibitor of the enzyme glucosylceramide synthase (GCS), successfully delays the onset of motor deficits, improves longevity, and rescues some of the cerebellar abnormalities (e.g., Purkinje cell death) seen in another lysosomal disease known as Niemann-Pick type C (NPC). Given the similarities in pathology between MLIV and NPC, we examined whether miglustat would be efficacious in ameliorating disease progression in MLIV. Using a full mucolipin-1 knockout mouse (Mcoln1-/-), we found that early miglustat treatment delays the onset and progression of motor deficits, delays cerebellar Purkinje cell loss, and reduces cerebellar microgliosis characteristic of MLIV disease. Quantitative mass spectrometry analyses provided new data on the GSL profiles of murine MLIV brain tissue and showed that miglustat partially restored the wild type profile of white matter enriched lipids. Collectively, our findings indicate that early miglustat treatment delays the progression of clinically relevant pathology in an MLIV mouse model, and therefore supports consideration of miglustat as a therapeutic agent for MLIV disease in humans.
Keywords: Animals; myši transgenní; Cell Count; pohybové poruchy; Psychomotor Performance; Gliosis; mozeček; CD antigeny; Mice, Transgenic; Retina; Glycosphingolipids; Mucolipin-1; Mucolipidosis type IV; Enzyme Inhibitors; psychomotorický výkon; Lipid Metabolism; Mice; Miglustat; Exploratory Behavior; Transient Receptor Potential Channels; 1-deoxynojirimycin; myši; metabolismus lipidů; proteiny nervové tkáně; Antigens, CD; Mucolipidoses; mukolipidózy; Nerve Tissue Proteins; modely nemocí na zvířatech; inhibitory enzymů; Disease Models, Animal; Cerebellum; Purkinje Cells; počet buněk; pátrací chování; Purkinje cells; retina; Movement Disorders; zvířata; Purkyňovy buňky; Mice, Inbred C57BL; Lysosomal storage disease; glióza; 1-Deoxynojirimycin; Small molecule therapy; kationtové kanály TRP; myši inbrední C57BL